An evaluation of alcohol attendances to an inner city emergency department before and after the introduction of the UK Licensing Act 2003 - Perkins TJ; Durnford AJ; Perry JM (BMC, 2008)
Abstract Background The Licensing Act 2003 (The Act) was implemented on the 24th November 2005 across England and Wales. The Act allowed more flexible and longer opening hours for licensed premises. We investigated the effect of The Act on alcohol related attendances to an inner city emergency department in Birmingham, UK. Methods We compared the proportion and time of alcohol related emergency department attendances in one week periods in January 2005 and 2006, before and after the implementation of The Licensing Act 2003. An alcohol related attendance was defined as any attendance where there was any documentation of the patient having consumed alcohol before presenting to the emergency department, if they appeared intoxicated on examination, or if alcohol attributed to their final diagnosis. Results The total weekly attendances increased slightly from 1,912 in 2005 to 2,146 in 2006. There was non-significant reduction in the proportion of alcohol related attendances between 2005 (3.6%) and 2006 (2.9%). A significantly greater proportion of attendances occurred at the weekend between 18.00 and 23.59 in 2005 (61.4%) than in 2006 (17.2%). There was a corresponding significant increase in the weekend proportion of attendances occurring between 03.00 to 05.59 in 2006. Conclusion Our findings show that there was a change in the pattern of alcohol related attendances to the emergency department around the time of implementation of the Licensing Act 2003, which has implications for delivery of emergency department services.